Optimization and Improvement of Electric Drive Valve Diagnostics Process During Pre-Commissioning Activities at NPP Units Under Construction - Z. O. Kavrishvili; V. L. Rachkov (Глобальная ядерная безопасность)
The article discusses the need for technical diagnostics of electric drive stop valves, and there are presented applied methods for evaluating the technical condition. In addition, an approach to the organization of commissioning works related to the configuration of electric drive valves is revealed, based on their combination with diagnostic support, which allows to improve the quality and efficiency of autonomous and complex commissioning as well as to increase the effectiveness of technical management of hydraulic tests and reduce their duration.